NEONATAL SIDE EFFECTS DURING PATIENT CONTROLLED INTRAVENOUS REMIFENTANIL FOR LABOR ANALGESIA - Karadjova, Dafina; Sivevski, Atanas; Ivanov, Emilija; Kjaev, Ivo; Spasova R; Mehmedovic, Nadica (Department of Anaesthesia and Reanimation, Faculty of Medicine “Ss. Cyril and Methodius” University in Skopje, 2020)
Introduction: Remifentanil is becoming more and more popular as alternative method for labor analgesia. There are limited studies about the neonatal safety of remifentanil for labor analgesia. Materials and Methods: Our study included 80 pregnant women, at term, receiving intravenous PCA with remifentanil for labor analgesia. Our primary goal was to examine neonatal safety when using remifentanil. During analgesia fetus was monitored through continuous cardiotocography recording. After delivery we recorded neonatal Apgar scores in 1st, 5th and 10th minute, acid-base status, use of naloxone and any neonatal resuscitation. Parturients all the time during labor analgesia have one-to-one care and complete haemodynamic monitoring (SaO2, respiratory rate, non-invasive blood pressure, and heart rate). Results: Fetal heart rate (FHR) abnormalities were recorded in 12 patients, 4 of them had pathological continuous cardiotocograph (CTG) records. The most common Apgar score in the 1st minute was 8, in the 5th it was 9 and in the 10th minute it was 10. Intermediate values of all parameters from the umbilical acid-base status of newborns were within normal limits. Conclusion: Neonatal side effects during patient-controlled intravenous analgesia with remifentanil are minimal. One-to-one care, appropriate continuous monitoring of the parturient and neonate with available resuscitation kit are mandatory